2019
DOI: 10.1177/1753193419841278
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of bone graft surgery for nonunion of fractures of the scaphoid

Abstract: Data on 806 patients undergoing bone graft surgery for a scaphoid fracture nonunion were retrospectively collected at 19 centres in the United Kingdom. Each centre contributed at least 30 cases. Sufficient data were available in 462 cases to study factors that influenced the outcome of surgery. Overall union occurred in at least 69%, and nonunion in at least 22%, with 9% of cases having ‘uncertain union status’. Union appeared to be adversely influenced by smoking and the time between acute scaphoid fracture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Whether the greater technical difficulty of PVBGs resulted in more complications could not be clarified. Our finding are consistent with many recent published studies 43,48 . In Ammori et al .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Whether the greater technical difficulty of PVBGs resulted in more complications could not be clarified. Our finding are consistent with many recent published studies 43,48 . In Ammori et al .…”
Section: Discussionsupporting
confidence: 94%
“…In Ammori et al . 's 48 retrospective study, data on 806 patients treated with bone graft surgery for a scaphoid fracture non‐union were collected at 19 centres. The results demonstrated type of bone graft (vascular versus non‐vascular; iliac crest versus distal radius) did not appear to influence outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This review is in line with best practice recommendations from the Cochrane guidelines, which cite that the median time for a review to require an update is 5.5 years, 90 and state that an update may be indicated if the research question is still relevant; there is new available evidence that has the potential to change or clarify findings. 91 There is still considerable debate regarding the optimal graft choice for scaphoid nonunion management, 75 and our update adds a further 30 studies to the most recent comparable review. 7 Despite these additions and the evolving knowledge of scaphoid fractures in recent years, there does not appear to be improved union rates over the last decade, and the rates of union with compression screws were not significantly different from other techniques.…”
Section: Discussionmentioning
confidence: 87%
“…There is no agreement in the definition of radiological union after scaphoid fracture surgery. Nonunion was defined as a fracture that had not united within 12 weeks of the acute injury based on plain radiographs or computed tomography (CT) scans [39]. One review found that the radiological features of union are the absence of bridging trabeculae [40] or the absence of a complete gap between the fracture fragments on any image, as well as no evidence of loosening of the fixation screw or wires [41].…”
Section: Discussionmentioning
confidence: 99%